2020
DOI: 10.2147/ijn.s274842
|View full text |Cite
|
Sign up to set email alerts
|

<p>pH-Responsive Fluorescence Enhanced Nanogel for Targeted Delivery of AUR and CDDP Against Breast Cancer</p>

Abstract: Introduction Auraptene (AUR), a natural bioactive prenyloxy coumarin, is a highly pleiotropic molecule that can bind to the MT1 receptor and can effectively reduce the proliferation and migration of breast cancer cells. Cisplatin (CDDP), as the first synthetic platinum-based anticancer drug, is widely used in the clinic due to its definite mechanism and therapeutic effect on diverse tumors. However, both of AUR and CDDP exhibit some disadvantages when used alone, including poor solubility, low bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…Cancer treatment [ 186] Nanogel HA Paclitaxel Enzyme-sensitive targeting Breast cancer treatment [ 187] Nanogel HA and 𝛽-CD derivative Auraptene and cisplatin pH-responsive, targeted delivery Synergistic therapy for breast cancer and cell imaging [ 188] Nanogel Poly (ethylene glycol) conjugated HA Cytochrome C Hypoxia response CD44 mediated tumor targeting [ 189] Nanogel Pluronic L61 linked HA Acid-sensitive capacity Cancer treatment [ 190] Nanogel HA, cisplatin, cancer cell membrane…”
Section: Cancer Treatmentmentioning
confidence: 99%
“…Cancer treatment [ 186] Nanogel HA Paclitaxel Enzyme-sensitive targeting Breast cancer treatment [ 187] Nanogel HA and 𝛽-CD derivative Auraptene and cisplatin pH-responsive, targeted delivery Synergistic therapy for breast cancer and cell imaging [ 188] Nanogel Poly (ethylene glycol) conjugated HA Cytochrome C Hypoxia response CD44 mediated tumor targeting [ 189] Nanogel Pluronic L61 linked HA Acid-sensitive capacity Cancer treatment [ 190] Nanogel HA, cisplatin, cancer cell membrane…”
Section: Cancer Treatmentmentioning
confidence: 99%
“…Additionally, it demonstrated a selective cytotoxicity to breast cancer cells compared to normal ones, which is a great indicator of biosafety. This is enhanced by the in vivo results, since the nanogel was able to reduce tumor volume while showing reduced systemic toxicity [ 52 ]. Nanogel application in theranostics has been demonstrated by Pan et al [ 53 ].…”
Section: Ha-based Hydrogelmentioning
confidence: 99%
“…It is known that there are abundant enzymes, including proteolytic enzymes, lipase, lysosomal enzymes, matrix metalloproteinases, and hyaluronidase. The enzyme possesses efficient and highly specific catalysts, which have inspired various enzyme-responsive nanogels for drug/protein delivery and triggered release in tumor site. For example, hyaluronic acid (HA) could intrinsic target toward CD44-overexpressed tumor cells. , It can be degraded when triggered by extracellular overexpressed hyaluronidases (HAase) in tumor tissue. As shown in Figure , Wang et al reported P-5m peptide encapsulated enzyme-responsive nanogels based on PNIPAM prepared by free radical precipitation polymerization .…”
Section: General Overview Of Stimulus Response For Cancer Therapymentioning
confidence: 99%
“…29−31 For example, hyaluronic acid (HA) could intrinsic target toward CD44-overexpressed tumor cells. 124,125 It can be degraded when triggered by extracellular overexpressed hyaluronidases (HAase) in tumor tissue. As shown in Figure 5, Wang et al reported P-5m peptide encapsulated enzyme-responsive nanogels based on PNIPAM prepared by free radical precipitation polymerization.…”
Section: General Overview Of Stimulus Responsementioning
confidence: 99%